Knowledge Management Practices in the Universities: A Qualitative Inquiry - Erstu Tarko Kassa; Jing Ning (SAGE Open)
The study used qualitative analysis techniques to examine knowledge management practices in Ethiopian public research universities. The study data were gathered through interviews with 18 key informants from public research universities in Addis Ababa, Hawasa, and Arba Mich. The collected data were analyzed using MAXQDA software. Thematic analysis was used to categorize the themes. The study’s findings revealed that knowledge management practices (knowledge creation, sharing, and transfer) in universities are practised with limited effort. Factors such as human resources practices, leadership, institutional, resources, and infrastructure influence university knowledge management practices. Based on the study analysis, a knowledge management framework was established, and codes were generated in this study using the software. Knowledge-based views and institutional theories are supported by the study’s results.